Toward a pecking order theory of strategic resource deployment - William Schulze; David Deeds; Robert Wuebker; Roman Kräussl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2015)
A premise of the capabilities perspective in strategy is that firm-specific capabilities allow some firms to be unusually adept at exploiting growth opportunities. Since few firms have the capacity to internally generate the quantity or variety of strategic resources needed to exploit growth opportunities, the ability to externally acquire complementary resources is critical to the acquisition of competitive advantage. However, the external sourcing of resources exposes the firm's strategic resources to risks of expropriation. We argue this threat gives capable firms incentive to use internally generated strategic resources to pursue growth opportunities before turning to external sources. A pecking order theory of strategic resource deployment is implied. Data from a 22-year sample of cross-border investment partnership decisions made by U.S.-based venture capital firms lend support to our theory.
urn:nbn:de:hebis:30:3-386645
Keywords: 330; Resource Acquisition; Dynamic Capabilities; Venture Capital